Evaluating urban water management using a water metabolism framework: A comparative analysis of three regions in Korea - Jeong, Seongpil; Park, Jooyoung (ELSEVIER, 2020)
As climatic and societal changes increase the prominence of water insecurity, sustainable urban water management focusing on water efficiency and reuse is an increasingly significant issue in Korea and elsewhere. This study uses the urban water metabolism framework to examine patterns of water flows in urbanized areas and evaluate water management performance in three Korean regions: Seoul (a metropolitan city), Ulsan (an industrial city), and Jeju (an urbanized agricultural province). Constructed water metabolism models showed distinct water use patterns and performance across each region in 2015. Seoul largely relied on surface water, while the residential sector's dominant use of water implies high greywater use and wastewater recycling potential. Ulsan relied on abstracting river water, with lower water availability of the river making Ulsan's water system less self-sustaining and more vulnerable to climatic risks than Seoul's. Facing higher water use intensity due to high industrial demand, Ulsan actively promotes industrial wastewater recycling. Jeju showed the highest water use intensity because of the presence of intensive agricultural activities. Nonetheless, Jeju sourced 76% of its water from internal sources, with its water system considered to be the most self-sustaining. These results suggest that the water metabolism framework helps facilitate more holistic understandings and evaluations of the water performance of cities.
Keywords: SUBSTANCE FLOW-ANALYSIS; MASS-BALANCE; TOOL